7-Hydroperoxycholesterol and its products in oxidized low density lipoprotein and human atherosclerotic plaque - A J Brown; S L Leong; R T Dean; W Jessup (Journal of Lipid Research, 1997)
7-Hydroperoxycholesterols (7OOHs) are intermediates in cholesterol oxidation and potential cytotoxins. A normal-phase HPLC method with UV (205 nm) detection was developed that could resolve 7 alpha OOH, 7 beta OOH, 7-ketocholesterol (7K), and the epimeric 7-hydroxycholesterols (7OHs). 7OOH formation was investigated when LDL was exposed to four different oxidizing systems: Cu2+; Ham's F-10; mouse peritoneal macrophages in Ham's F-10; and a metal-independent peroxyl-radical generating system (AAPH). With all four oxidizing systems, 7OOH (both free and esterified, mostly as the beta-isomer) was the major oxysterol formed at early times, with 7K dominating at later stages (> or = 24 h) in Cu-oxLDL. When LDL was oxidized in the presence of cells there was transfer of free oxysterols from LDL to the cells. Negligible 7OOH, but significant amounts of 7OH, accumulated in the cells suggesting efficient cellular reduction of 7OOH. Lipid extracts from eight plaque samples obtained from patients undergoing carotid endarterectomy were analyzed. Only trace amounts of 7OOH (< 0.02% of total cholesterol) could be detected using this normal-phase HPLC method with UV detection or with a more sensitive reverse-phase method utilizing chemiluminescence detection. 7K was the major 7-oxygenated sterol detected, at least 20-fold in excess of that calculated for 7OOH, followed by 7 beta OH and 7 alpha OH. The trace concentrations of 7OOH in plaque indicate its lability in biological/cellular systems and may signify the ability of cells in the artery wall to metabolize it further.